Effect of ivermectin on the prevalence of gastrointestinal parasites in Jamuna basin sheep: Effect of ivermectin in Jamuna basin sheep - Sultana, S; Hossain, MA; Sun, MA; Akhter , S; Hashem, MA (SAARC Journal of Agriculture, 2022)
The effect of ivermectin on the prevalence of gastrointestinal parasites of Jamuna basin sheep was investigated in relation to the areas, flock sizes and rearing systems. A total 420 faecal samples were examined microscopically by using Stoll’s ova dilution technique from June to December 2020. The number of eggs per gram of feces was calculated and it ranged from 100-500.The study showed that 100% sheep were found to be infected with one or more species of parasites. Four types of parasites were identified. In grazing animals, stomach worm, Paramphistomum worm, Fasciola and install feeding, stomach worm and Trichuris were found. The prevalence of parasites in grazing on 0 day was stomach worm 20%, Paramphistomum worm10% whereas in stall feeding it was stomach worm 15% and Trichuris 10%. In 15 days, in all grazing animals stomach worm was 10% and Paramphistomum worm 10% whereas in stall feeding it was stomach worm 5%. On 30th day, in grazing animals, stomach worm 15%, and Paramphistomum worm 10% were present, whereas in stall feeding it was stomach worm 10%, and Paramphistomum 10%. The highest prevalence of stomach worm was 20%, whereas Paramphistomum was the lowest with 10% as seen ingrazing animals. Stomach worm with 15% was the highest and theTrichuris with 10% was the lowest in stall feeding animals. Prevalence of parasites increased with the flock size on 0 day and ivermectin injection reduced the prevalence in 15 days and later it increased after 30 days of interval. The prevalence was higher in char area (35%) than the hilly area (15%). The sheep were more affected in grazing (25%) than stall feeding (20%). In conclusion, the use of ivermectin injection reduced the prevalence of gastrointestinal parasites up to one month in sheep. SAARC J. Agric., 20(2): 235-245 (2022)